Tacit Knowledge: Some Suggestions for Operationalization - Ambrosini, Veronique; Bowman, Cliff (Blackwell Publishing Ltd, 2001)
With the emergence of the resource-based view of the firm and of the concept of core competencies, intangible resources, and tacit knowledge in particular have been argued to occupy a central place in the development of sustainable competitive advantage. This is because tacit knowledge is argued to be difficult to imitate, to substitute, to transfer and it is rare. However, there is little empirical research to support this theoretical proposition. Tacit knowledge has so far resisted operationalization. This paper sets out to define the term tacit knowledge and proposes to redefine it, within the context of the resource-based view of the firm, as tacit skills. A methodology (based on causal mapping, self- Q and storytelling) for empirically researching the subject is outlined.